Thermoconvective Stability of a Ferrofluids in Presence of Magnetic Field (Journal of Scientific Research, 2016)
We have carried out a theoretical analysis of the linear thermoconvective stability of a ferrofluid, which is confined between two horizontal plates maintained at different constant temperatures and which is subject to an external uniform magnetic field in the vertical direction. The effects of the spin viscosity, vortex viscosity and magnetization relaxation are considered and discussed. The eigenvalue problem is solved by employing the Chebyshev pseudospectral method. It is found that the presence of magnetic field complements the buoyancy force in destabilizing the fluid at lower values of the magnetic field only and when the applied field is increased, the effect is reversed and the flow becomes more stable.